Can preventive care activities in general practice be sustained when financial incentives and external audit plus feedback are removed? ACCEPt-able: a cluster randomised controlled trial protocol. (December 2015) - Hocking, Jane; Temple-Smith, Meredith; van Driel, Mieke; Law, Matthew; Guy, Rebecca; Bulfone, Liliana; Wood, Anna; Low, Nicola; Donovan, Basil; Fairley, Christopher; Kaldor, John; Gunn, Jane
Abstract Background Financial incentives and audit plus feedback on performance are two strategies commonly used by governments to motivate general practitioners (GP) to undertake specific healthcare activities. However, in recent years, governments have reduced or removed incentive payments without evidence of the potential impact on GP behaviour and patient outcomes. This trial (known asACCEPt-able ) aims to determine whether preventive care activities in general practice are sustained when financial incentives and/or external audit plus feedback on preventive care activities are removed. The activity investigated is annual chlamydia testing for 16- to 29-year-old adults, a key preventive health strategy within this age group. Methods/design ACCEPt-able builds on a large cluster randomised controlled trial (RCT) that evaluated a 3-year chlamydia testing intervention in general practice. GPs were provided with a support package to facilitate annual chlamydia testing of all sexually active 16- to 29-year-old patients. This package included financial incentive payments to the GP for each chlamydia test conducted and external audit plus feedback on each GP's chlamydia testing rates. ACCEPt-able is a factorial cluster RCT in which general practices are randomised to one of four groups: (i) removal of audit plus feedback—continue to receive financial incentive payments for each chlamydia test; (ii) removal of financial incentive payments—continue to receive audit plus feedback; (iii) removal of financial incentive payments and audit plus feedback; and (iv) continue financial incentive payments and audit plus feedback. The primary outcome is chlamydia testing rate measured as the proportion of sexually active 16- to 29-year-olds who have a GP consultation within a 12-month period and at least one chlamydia test. Discussion This will be the first RCT to examine the impact of removal of financial incentive payments and audit plus feedback on the chlamydia testing behaviour of GPs. This trial is particularly timely and will increase our understanding about the impact of financial incentives and audit plus feedback on GP behaviour when governments are looking for opportunities to control healthcare budgets and maximise clinical outcomes for money spent. The results of this trial will have implications for supporting preventive health measures beyond the content area of chlamydia. Trial registration The trial has been registered on the Australian and New Zealand Clinical Trials Registry (ACTRN12614000595617 ).